2020
DOI: 10.1007/s00267-020-01324-2
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Proposal for the Inventory and Assessment of Geomorphosites: An Integrated Approach focused on Territorial Management and Geoconservation

Abstract: E. (2020). Methodological proposal for the inventory and assessment of geomorphosites: An integrated approach focused on territorial management and geoconservation. Environmental Management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…The IELIG method [40] provides the protection priority value, which is essential for establishing improvement strategies. Additionally, the chosen methods have parameters that include the types of interest of CNP and have the aesthetic value within the evaluation, which is an important factor in geomorphosites [103].…”
Section: Discussionmentioning
confidence: 99%
“…The IELIG method [40] provides the protection priority value, which is essential for establishing improvement strategies. Additionally, the chosen methods have parameters that include the types of interest of CNP and have the aesthetic value within the evaluation, which is an important factor in geomorphosites [103].…”
Section: Discussionmentioning
confidence: 99%
“…These elements describe the form and quality of the area, and they are common throughout the Earth, while other elements of main values (volcanos, caves, weathering mass, and structural elements) are connected to places with conditions that contribute to evolution of these processes. Additionally, soils were not mentioned above, as this element is considered to fall within the sphere of biological activity and will be studied in future research [3,10,[30][31][32][33][34][35]. Notably, soils represent the interface between abiotic and biotic nature and processes, with soil formation and type impacting on the geocultural aspects of societal development, such as evolution of agricultural practices.…”
Section: Methodsmentioning
confidence: 99%
“…The geoconservation community must work to ensure that geographic heritage conservation in protected areas gains more popularity on local, national, and international agendas for nature, sustainable development, and human well-being [9]. Over the past two decades, several quantitative and qualitative methods proposed how to classify geodiversity and geoheritage [11][12][13]. Due to their geographical nature and disciplinary novelty, geoheritage studies are more common in temperate regions than in tropical regions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Quesada-Román and Pérez-Umaña [20] studied the volcanic and paleoglacial geoheritage of the Miocene-Quaternary and the promotion of geotourism at Chirripó National Park in Costa Rica. Recently, Rosado-González et al [21] indicated that three geoparks (Chirripó in Costa Rica, Over the past two decades, several quantitative and qualitative methods proposed how to classify geodiversity and geoheritage [11][12][13]. Due to their geographical nature and disciplinary novelty, geoheritage studies are more common in temperate regions than in tropical regions [14].…”
Section: Introductionmentioning
confidence: 99%